2014
DOI: 10.1016/j.ajhg.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

AP1S3 Mutations Are Associated with Pustular Psoriasis and Impaired Toll-like Receptor 3 Trafficking

Abstract: Adaptor protein complex 1 (AP-1) is an evolutionary conserved heterotetramer that promotes vesicular trafficking between the trans-Golgi network and the endosomes. The knockout of most murine AP-1 complex subunits is embryonically lethal, so the identification of human disease-associated alleles has the unique potential to deliver insights into gene function. Here, we report two founder mutations (c.11T>G [p.Phe4Cys] and c.97C>T [p.Arg33Trp]) in AP1S3, the gene encoding AP-1 complex subunit σ1C, in 15 unrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(180 citation statements)
references
References 30 publications
5
172
0
3
Order By: Relevance
“…Slc16a8 is a member of a family of proton- coupled monocarboxylate transporters that mediate lactate transport across the cell membrane, and Slc16a8 is highly expressed in the RPE, required for visual function and associated with AMD (Daniele et al, 2008;Philp et al, 1998;Priya et al, 2012), and has been experimentally shown to be upregulated by miR-204 (Adijanto et al, 2012). Genes with as yet unknown functions in the RPE, such as Ap1s3, which encodes a subunit of adaptor protein complex, should also be considered when attempting to identify the underlying cause of the phenotype following miRNAs loss from the RPE, as this subunit was recently shown to play a role in the endosomal translocation of signaling components involved in inflammation in skin keratinocytes (Boehm and Bonifacino, 2002;Setta-Kaffetzi et al, 2014). Previous studies conducted in cultured human RPE cells suggested that miR-204 is essential for the maintenance of RPE specification, as without miR-204 the cells lose their epithelial identity and undergo EMT (Adijanto et al, 2012).…”
Section: Dicer1 Is Dispensable For Rpe Fate and Survival During Develmentioning
confidence: 99%
“…Slc16a8 is a member of a family of proton- coupled monocarboxylate transporters that mediate lactate transport across the cell membrane, and Slc16a8 is highly expressed in the RPE, required for visual function and associated with AMD (Daniele et al, 2008;Philp et al, 1998;Priya et al, 2012), and has been experimentally shown to be upregulated by miR-204 (Adijanto et al, 2012). Genes with as yet unknown functions in the RPE, such as Ap1s3, which encodes a subunit of adaptor protein complex, should also be considered when attempting to identify the underlying cause of the phenotype following miRNAs loss from the RPE, as this subunit was recently shown to play a role in the endosomal translocation of signaling components involved in inflammation in skin keratinocytes (Boehm and Bonifacino, 2002;Setta-Kaffetzi et al, 2014). Previous studies conducted in cultured human RPE cells suggested that miR-204 is essential for the maintenance of RPE specification, as without miR-204 the cells lose their epithelial identity and undergo EMT (Adijanto et al, 2012).…”
Section: Dicer1 Is Dispensable For Rpe Fate and Survival During Develmentioning
confidence: 99%
“…In fact, the power of the familial PV, APP and GPP samples exceeded 95% (Figure 1). This is in keeping with previous analyses of the APP and GPP cohorts, which allowed us to identify a number of low-frequency mutations (Setta-Kaffetzi et al, 2013;Setta-Kaffetzi et al, 2014).…”
Section: Resultsmentioning
confidence: 84%
“…Pityriasis rubra pilaris was diagnosed on the basis of established criteria (Judge et al, 2004). All patients with pustular psoriasis had been previously screened for IL36RN and AP1S3 mutations, so as to exclude any subjects carrying disease alleles at known loci (Onoufriadis et al, 2011;Setta-Kaffetzi et al, 2014). Individuals who were affected by psoriasis vulgaris and had at least one first-degree relative with the same disease were considered cases of familial PV (Supplementary Table 1).…”
Section: Subjectsmentioning
confidence: 99%
“…62,63 Recently, whole exome sequencing was used to identify two heterozygous mutations in AP1S3, encoding a small subunit of AP-1 complex, which are associated with pustular psoriasis. 64 Silencing of AP1S3 was demonstrated to disrupt the endosomal translocation of TLR-3, which resulted in inhibition of TLR-3-mediated IFN-b induction. Given that IFN-b downregulates the production of IL-1 65 this study further supports a potential role for IL-1 blockade for treatment of pustular variants of psoriasis.…”
Section: Other Subtypes Of Psoriasismentioning
confidence: 98%